The effect of physical activity in differentiated STEAM projects on science learning and 21st-century skill development skills - Arfilia Wjayanti; Wiyanto Wiyanto; Saiful Ridlo; Parmin Parmin (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective: This study compares differentiated STEAM projects in science learning using science experiments, STEAM integration, and physical activity integration, as well as students' perceptions of the role of physical activity. This study also examines how these physical activities motivate kids and develop 21st-century abilities like teamwork, creativity, and critical thinking.